OP0059 Efficacy and safety of intra-articular sprifermin in symptomatic radiographic knee osteoarthritis: pre-specified analysis of 3-year data from a 5-year randomised, placebo-controlled, phase ii study. (12th June 2018) - Hochberg, M.; Guermazi, A.; Guehring, H.; Aydemir, A.; Wax, S.; Fleuranceau-Morel, P.; Reinstrup Bihlet, A.; Byrjalsen, I.; Ragnar Andersen, J.; Eckstein, F.
Abstract : Background: Sprifermin, a novel recombinant human fibroblast growth factor 18, is currently being investigated as a potential disease-modifying osteoarthritis (OA) drug. Two-year results of the 5 year phase II FORWARD study showed a statistically significant dose-dependent cartilage thickness increase in the total femorotibial joint (TFJ), and in the medial, lateral and central medial sub-region TFJ compartments by quantitative magnetic resonance imaging (qMRI). Objectives: Here we report the pre-specified 3 year results. Methods: Patients (pts) aged 40–85 years with symptomatic radiographic knee OA, Kellgren-Lawrence grade (KLG) 2 or 3, and medial mJSW ≥2.5 mm in the target knee were randomised (1:1:1:1:1) to receive 3 weekly i.a. injections with double-blinded placebo (PBO) or sprifermin, administered q6mo (0, 6, 12, and 18 months) or q12mo (0 and 12 months). The primary endpoint was the change in TFJ cartilage thickness from baseline (BL) to Year 2 with pre-specified analyses at Year 3. The intent-to-treat (ITT) population (all randomised pts) was used for non-qMRI endpoints; and the modified ITT population (all ITT pts with BL and ≥1 post-treatment MRI up to Year 2) for qMRI endpoints. Results: 549 pts were randomised (median age 65 years, 69% women, 80% white, 69% KLG2, and 70% predominantly medial disease); of which 18.4% (sprifermin) and 24.1% (PBO) discontinued the study within 3 years. TFJ cartilage thickness decreased from Year 2 to 3 in all treatment groups; however, the 0.05 mm difference between sprifermin 100 µg q6mo and PBO was maintained (0.00 vs −0.05 mm; p<0.001; figure 1a). Additionally, significant differences in mean cartilage thickness change from BL to Year 2 were maintained up to Year 3 with sprifermin 100 µg vs PBO in both the medial (100 µg q6mo −0.01 vs −0.06 mm; p=0.025) and lateral TFJ compartments (100 µg q6mo and q12mo:+0.01 and 0.00 vs −0.04 mm; p<0.001 and p=0.003, respectively), and central medial (100 µg q6mo:+0.009 vs −0.084 mm; p=0.008; figure 1b) and central lateral (100 µg q6 and q12mo:+0.038 and+0.017 vs −0.053 mm; p<0.001 and p=0.003, respectively) TFJ sub-regions. The significant mean change from BL to Year 2 in lateral (but not medial) mJSW by X-ray was maintained up to Year 3 with both sprifermin 100 µg groups vs PBO (100 µg q6 and q12mo:+0.13 and+0.10 vs −0.11 mm; p=0.014 and p=0.040, respectively). By Year 2 total WOMAC scores were improved by 50% in all treatment groups including PBO, and maintained up to Year 3 (18 months after last injection) without a significant difference between treatment groups. AEs and serious AEs remained balanced between groups at Years 2 and 3. Conclusions: The 3 year results of the FORWARD study are consistent with the 2 year results: although cartilage thickness declined in all treatment groups between Year 2 and 3, the difference at Year 2 with sprifermin 100 µg vs PBO was maintained up to Year 3. Based on qMRI sprifermin is effective at increasing cartilage thickness in a dose-dependent manner in knee OA patients, and has an acceptable safety profile. Disclosure of Interest: M. Hochberg Consultant for: Bioiberica SA, Bristol Myers Squibb, EMD Serono, Inc., Galapagos, IBSA Biotechniq SA, Novartis Pharma AG, Pfizer Inc., Plexxikon, Samumed LLC, Theralogix LLC and TissueGene Inc, A. Guermazi Consultant for: OrthoTrophix, GE Healthcare, Merck Serono, AstraZeneca, Sanofi, TissueGene and Pfizer, Employee of: Boston Imaging Core Lab, LLC, H. Guehring Employee of: Merck KGaA, A. Aydemir Employee of: EMD Serono, Inc., S. Wax Employee of: EMD Serono, Inc., P. Fleuranceau-Morel Employee of: EMD Serono, Inc., A. Reinstrup Bihlet Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, I. Byrjalsen Employee of: Nordic Bioscience, J. Ragnar Andersen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, F. Eckstein Shareholder of: Chondrometrics GmbH, Consultant for: Merck KGaA, Samumed LLC, Abbvie, Bioclinica, TissueGene, Servier and Roche, Employee of: Chondrometrics GmbH